Daclatasvir with sofosbuvir and ribavirin for hepatitis C virus infection with advanced cirrhosis or post‐liver transplantation recurrence. Issue 5 (7th March 2016) - Poordad, Fred; Schiff, Eugene R.; Vierling, John M.; Landis, Charles; Fontana, Robert J.; Yang, Rong; McPhee, Fiona; Hughes, Eric A.; Noviello, Stephanie; Swenson, Eugene S.
Abstract : Chronic hepatitis C virus (HCV) infection with advanced cirrhosis or post‐liver transplantation recurrence represents a high unmet medical need with no approved therapies effective across all HCV genotypes. The open‐label ALLY‐1 study assessed the safety and efficacy of a 60‐mg once‐daily dosage of daclatasvir (pan‐genotypic NS5A inhibitor) in combination with sofosbuvir at 400 mg once daily (NS5B inhibitor) and ribavirin at 600 mg/day for 12 weeks with a 24‐week follow‐up in two cohorts of patients with chronic HCV infection of any genotype and either compensated/decompensated cirrhosis or posttransplantation recurrence. Patients with on‐treatment transplantation were eligible to receive 12 additional weeks of treatment immediately after transplantation. The primary efficacy measure was sustained virologic response at posttreatment week 12 (SVR12) in patients with a genotype 1 infection in each cohort. Sixty patients with advanced cirrhosis and 53 with posttransplantation recurrence were enrolled; HCV genotypes 1 (76%), 2, 3, 4, and 6 were represented. Child‐Pugh classifications in the advanced cirrhosis cohort were 20% A, 53% B, and 27% C. In patients with cirrhosis, 82% (95% confidence interval [CI], 67.9%‐92.0%) with genotype 1 infection achieved SVR12, whereas the corresponding rates in those with genotypes 2, 3, and 4 were 80%, 83%, and 100%, respectively; SVR12 rates were higher in patients with Child‐Pugh class A or B, 93%, versus class C, 56%. In transplant recipients, SVR12 was achieved by 95% (95% CI, 83.5%‐99.4%) and 91% of patients with genotype 1 and 3 infection, respectively. Three patients received peritransplantation treatment with minimal dose interruption and achieved SVR12. There were no treatment‐related serious adverse events. Conclusion : The pan‐genotypic combination of daclatasvir, sofosbuvir, and ribavirin was safe and well tolerated. High SVR rates across multiple HCV genotypes were achieved by patients with post‐liver transplantation recurrence or advanced cirrhosis. (Hepatology 2016;63:1493‐1505)